Acute Effect of Single Bout Aerobic exercise with and without Blood Flow Restriction on Hemodynamic and Coagulation Indicators in Hypertension Disease - Zahra Karimi Ahmadabadi; Javad Nemati; Seyed Hesamuddin Mousavinia; Rasoul Rezaei (Shahid Beheshti University, 2022)
Purpose: Depending on the intensity and duration of activity, aerobic exercise leads to changes in hemodynamic factors and the hemostatic system in hypertensive patients, which can be expected to change if blood flow is restricted during exercise. Therefore, the purpose of the present study was to investigate the response of some hemodynamic and coagulation indicators to aerobic exercise with and without blood flow restriction in hypertensive patients.Methods: 10 hypertensive patients participated in two sessions of aerobic exercise (five bouts, two minutes of exercise at a speed of four km / h /one minute of inactive recovery) with and without blood flow restriction in a cross-over design. Blood pressure was measured before, immediately, five, 10, 15, 30 and 60 minutes after exercise. Platelet counts, Prothrombin Time and activated Partial Thromboplastin Time were taken before, immediately, 30 minutes and 24 hours after exercise. Heart rate and rate of perceived exertion were also measured at different times of exercise.Results: The effect of time was significant on all measured factors (P < 0.001) except platelet counts (P = 0.055), while the time-condition interaction was non-significant on other factors (P > 0.05) except heart rate (P = 0.011).Conclusion: Based on the results, blood flow restriction increased hemodynamic factors and decreased clotting time in hypertensive patients, but the differences between aerobic exercise with and without blood flow restriction were not significant, so it seems that exercise with limited blood flow does not pose an additional risk on the cardiovascular system and coagulation factors of middle-aged people with hypertension.